Are friends electric? Valuing the social costs of power lines using house prices - Tang, Cheng Keat (2024)
Overhead electrical power lines and pylons have long raised concerns regarding the effects of electromagnetic fields on health, noise pollution and the visual impact on rural landscapes. These issues are once again salient because of the need for new lines to connect sources of renewable energy to the grid. In this study we provide new evidence on the cost implied by these externalities, as revealed in house prices. We use a spatial difference-in-difference approach that compares price changes in neighborhoods that are close to overhead power-lines, before and after they are constructed, with price changes in comparable neighborhoods further away. Our findings suggest that the construction of new overhead pylons reduces prices by 3.9% for properties up to 1500 m away, suggesting the impacts extend further than previously estimated.